Adaptive Four-Channel Neuro-Fuzzy Control of a Master-Slave Robot. (1st March 2013) - Po-Ngaen, Watcharin
In bilateral control of tele-manipulation based on a conventional approach, there are deficiencies in stability robustness and manoeuvrability against variations in the dynamics of the master input device and the task environment. In this study, an adaptive four-channel neuro-fuzzy bilateral control scheme is proposed. To evaluate whether the proposed algorithm is a suitable technique for improving the robustness and manoeuvrability of tele-robot implementation, four-channel neuro-fuzzy and classical bilateral control frameworks have been investigated in a simulation experiment. Distinct bilateral control schemes in the form of four-channel intelligent control and the classic form of position–force and position -position have been implemented and compared using a one degree of freedom (DOF) master-slave system. The experimental results show that the application of a four-channel neuro-fuzzy control strategy effectively improves the overall performance.